More to fish farming than fish - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
international seminar in May 1994 in Brussels that was organized by CTA and the Belgian Royal Academy of Overseas Sciences with the collaboration of the FAO